Nano-biofortification for Improving Nutrient Status of Crop Plants - Imran, G. M.; Nalini, N.; Banoth, Sai Kumar; Malek, Faizan; Lakshman, Bharothu; Deepthi, P. Sowjanya (Chronicle of Bioresource Management, 2025)
Micronutrient malnutrition, often termed “hidden hunger,” remains a major global health concern, particularly in developing nations dependent on staple crops with limited nutritional diversity. Nanotechnology-enabled biofortification offers a revolutionary approach to enhancing the nutritional content of crops by using nanoscale materials for the precise and efficient delivery of essential micronutrients like zinc, iron, and silicon. Various types of Nanoparticles (NPs) such as (ZnO, Fe2O3 and Si-NPs) enhance nutrient uptake and translocation, including controlled release, increased solubility and activation of nutrient transporters. However, challenges such as potential toxicity, regulatory gaps and high costs are critically examined. Future directions focus on the development of smart, eco-friendly nanocarriers and integration with precision agriculture. Overall, nanotechnology-enabled biofortification emerges as a promising strategy to address nutritional security and promote sustainable agriculture.